DEVELOPMENT OF SOCIAL INTELLIGENCE OF FUTURE MANAGERS IN THE SYSTEM OF HIGHER EDUCATION - Olga Solovyova; Roman Tseev (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with the role and importance of social intelligence of the future managers in system of higher education. It is emphasized that the change of requirements for modern managers, as a subject of professional activity are changing requirements for its professionalization process that calls for innovative designing of the educational environment of high school. The essence of social intelligence and its place in the structure of professionally important qualities of the manager. Marked general orientation towards the development of social intelligence of students-managers in the system of higher education